式-003

 

 

\( S(xy) = \displaystyle \sum_{ i=1 }^n ( x_{ i } – \bar{ x })( y_{ i } – \bar{ y }) \)

\( S(xy) = \displaystyle \sum_{ i=1 }^n  x_{ i }y_{ i } – n \sum_{ i=1 }^n x_{ i } \sum_{ i=1 }^n y_{ i } \)

\( S(xy) = \displaystyle \sum_{ i=1 }^n  x_{ i }y_{ i } – \displaystyle\frac{\sum_{ i=1 }^n x_{ i } \sum_{ i=1 }^n y_{ i } }{ n } \)

\( S(xy) = – \displaystyle\frac{\sum_{ i=1 }^n x_{ i } \sum_{ i=1 }^n y_{ i } }{ n } \)

\( S(xy) = \displaystyle \sum_{ i=1 }^n  x_{ i }y_{ i } – \displaystyle\frac{ 1 }{ n } \sum_{ i=1 }^n x_{ i } \sum_{ i=1 }^n y_{ i } \)

 

\( \bar{ x } \)   \( V_{ x } \)   \( s_{ x } \)   \( z = ax + b \)   \( \bar{ z } = a \bar{ x } + b \)

\( V_{ z } = a^2 \cdot V_{ x } \)   \( s_{ z } = | a | s_{ x } \)